THE SANDWICH GENERATION: NAVIGATING MULTIDIMENSIONAL BURDENS AND BUILDING RESILIENCE IN SURAKARTA - Listiyanto Adi Nugroho (RADJA PUBLIKA, 2026)
The sandwich generation faces the dual burden of financially and emotionally supporting both aging parents and dependent children, a pressing issue in Indonesia given its high dependency ratio. This study aims to analyze the economic aspects, psychological impacts, and support systems experienced by the sandwich generation in Surakarta. Employing a qualitative descriptive approach, data were collected through semi-structured interviews with 3–5 purposively selected informants and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal three main conclusions. First, economically, the group bears a three-tiered financial burden for parents, children, and core household needs exacerbated by inflation, with uneven saving and investment capacities across income levels. Second, psychologically, they experience both negative impacts (stress, anxiety, guilt, exhaustion) and positive outcomes (inner satisfaction, meaning in life, strengthened family bonds, and acceptance), the latter serving as key resilience resources. Third, support from spouses and siblings is crucial, yet external support from government and workplaces remains unevenly accessible. This study concludes that while the sandwich generation endures significant multidimensional pressures, their resilience is sustained through a dynamic interplay of personal adaptation and available support systems. Expanding inclusive social protection and workplace flexibility is urgently recommended.